Dimensions of Heritage and Memory Multiple Europes and the Politics of Crisis, 1st Edition - Whitehead, Christopher; Eckersley, Susannah; Daugbjerg, Mads; Bozoğlu, Gönül (Taylor & Francis, 2019)
Dimensions of Heritage and Memory is a landmark contribution on the politics of the past in Europe today. The book explores the meanings of heritage in a time of crisis, when the past permeates social and political divisions, identity contests and official projects to forge a European community. Providing an overview of the literature and an analysis of the assumptions, values and philosophies embedded within European-level policy, the book explores different dimensions of heritage and memory, from official sites, museums and policy, to party politics, historical re-enactments and the everyday ways in which people use the past to make sense of who they are. The volume explores how different understandings of and attachments to the European past produce different 'Europes' in the present, accounting for today's tense social and political relations. The book also explores formative histories for European identities that are neglected or hidden because of political circumstances and non-official heritage. Contributors consider the meanings of interlocking crises, such as economic fallout, xenophobia and the fragmentation of the EU, for new understandings of Europe's past in the present. Dimensions of Heritage and Memory will be of great interest to researchers, academics and postgraduate students in the fields of heritage and memory studies, museum studies, history, cultural studies, sociology, anthropology and politics. The book will also be interesting to practitioners and cultural heritage policy-makers.